Activating killer immunoglobulin‐like receptors genes are associated with increased susceptibility to ankylosing spondylitis. (May 2015) - Díaz‐Peña, R.; Vidal‐Castiñeira, J. R.; Mulero, J.; Sánchez, A.; Queiro, R.; López‐Larrea, C.
Summary The aim of this study was to analyse the association of specific killer cell immunoglobulin‐like receptors (KIR) genes and haplotypes with susceptibility to ankylosing spondylitis (AS) and its different clinical manifestations in a Spanish population. The presence or absence of all KIR genes was studied for their association with AS. A total of 176 patients with AS and 435 healthy control subjects were selected for this study based on clinical criteria. The commercial KIR‐sequence‐specific oligonucleotides (SSO) typing kit was used to investigate KIR typing. Frequencies of KIR2DS1 and KIR3DS1 genes were increased significantly in patients compared with healthy controls [52·8 versus 38·2%, PBonf < 0·01, odds ratio (OR) = 1·81 (1·28–2·59); 51·7 versus 37·5%, PBonf < 0·01, OR = 1·79 (1·25–2·54)]. Moreover, the frequency of activating genotypes in the AS patient group was significantly higher than in the healthy control group (P < 0·05). KIR2DS1 and KIR3DS1, in addition to human leucocyte antigen (HLA)‐B27, may play an important role in the pathogenesis of AS. However, we show that the contribution of the KIR genes to AS susceptibility extends beyond the association with individual KIRs, with an imbalance between activating and inhibitory KIR genes seeming to influence the susceptibility to AS.